2015
DOI: 10.1039/c5ja00325c
|View full text |Cite
|
Sign up to set email alerts
|

Speciation of chromium by dispersive liquid–liquid microextraction followed by laser-induced breakdown spectrometry detection (DLLME–LIBS)

Abstract: Combination of dispersive liquid–liquid microextraction with laser-induced breakdown spectrometry for simultaneous pre-concentration, speciation and detection of Cr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The method was validated by spike recoveries from these samples. Gaubeur et al detected 124 the Cr by surface-enhanced LIBS (described in earlier publications from this research group) from an Al substrate to which 10 µL of the organic solvent had been applied and then dried. There are no details of this stage of the procedure, though the rest of the LIBS system is described in considerable detail.…”
Section: Chromiummentioning
confidence: 99%
“…The method was validated by spike recoveries from these samples. Gaubeur et al detected 124 the Cr by surface-enhanced LIBS (described in earlier publications from this research group) from an Al substrate to which 10 µL of the organic solvent had been applied and then dried. There are no details of this stage of the procedure, though the rest of the LIBS system is described in considerable detail.…”
Section: Chromiummentioning
confidence: 99%
“…A significant contribution has been made to the improvement of dispersive liquid‐liquid preconcentration procedures for speciation of chromium ions . Out of these methodologies, mostly characterized for reducing the time, consumption of potentially organic solvents, tedious multi stage operations, generation of waste in the laboratory, requirement of complex and large laboratory equipment that usually faced in preconcentration methods.…”
Section: Introductionmentioning
confidence: 99%
“…6 The most commonly performed analytical strategy for Cr monitoring involves two steps: (1) collection of water samples at the eld site followed by storage and transportation it to the laboratory, and (2) analysis using atomic spectrometry aer separation by one of a number of online or offline separation approaches, such as solid-phase extraction, liquid-liquid extraction, cloud-point extraction, or co-precipitation. [8][9][10][11][12][13][14] However, accurate speciation of Cr in natural water bodies is difficult, mainly due to matrix complexity and the instability of Cr redox species during sample collection, transport, and analysis. 15 For example, Meeravali et al 16 found that the concentration of Cr(III) increased by 135% and that of Cr(VI) decreased by 75% within 24 h when lake water samples were collected and stored at 4 C. This demonstrates that the concentrations of chemical species in particular redox states are inherently unstable in water and subject to change by re-equilibration upon reaction with other dissolved components.…”
Section: Introductionmentioning
confidence: 99%